MARDI GRAS THROUGH INSTAGRAM STORIES: HOW EPHEMERAL MEDIA SHAPE EVERYDAY ENGAGEMENTS WITH IDENTITY POLITICS - Cassidy, Elija; Matamoros Fernandez, Ariadna; Thomson, T.J. (AoIR Selected Papers of Internet Research, 2019)
A third of the world’s population is active on social media and a growing number is sharing ephemeral content on such platforms. Though originally pioneered by Snapchat, Instagram has come to dominate the ephemeral media market and, as of January 2019, boasts half a billion daily Instagram Stories users (Statista, 2019). Launched roughly 2.5 years ago, in August 2016, Instagram Stories offers people a novel way of communicating through sharing photos and videos that, by default, are only available for 24 hours and then disappear. This phenomenon presents unique challenges for researchers but also demands additional attention in order to understand contemporary forms of sociability and meaning-making. This study examines people’s everyday engagements with ephemeral media through an exploration of more than 400 Instagram stories created during the 2019 Sydney Gay and Lesbian Mardi Gras Festival. Through this empirical work, we aim to examine the place of ephemeral media in everyday communication and to start a public conversation around the Implications of “losing” ephemeral media and how this might impact archival practices for the study of historical events that get heavily mediated through digital media.